2021
DOI: 10.1177/00812463211061071
|View full text |Cite
|
Sign up to set email alerts
|

Cancer coping self-efficacy mediates the relationship between mental adjustment to cancer and health-related quality of life in persons with cancer

Abstract: Individuals with cancer experience significant levels of distress. Improving health-related quality of life of persons with cancer is a major focus in cancer treatment. This study investigated the mediating role of self-efficacy for coping with cancer in the relationship between mental adjustment to cancer and health-related quality of life among individuals with cancer. Two hundred and fourteen persons with cancer (male = 74, female = 140, mean age = 50.57) were recruited from a University Teaching Hospital, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The results also revealed that coping self‐efficacy can mediate the relationship between uncertainty intolerance and self‐perceived burden in patients diagnosed with cancer. No research has been found that is directly consistent with these results, but there are studies from which such results can be inferred 30,31 . Research by Onyedibe et al 30 .…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…The results also revealed that coping self‐efficacy can mediate the relationship between uncertainty intolerance and self‐perceived burden in patients diagnosed with cancer. No research has been found that is directly consistent with these results, but there are studies from which such results can be inferred 30,31 . Research by Onyedibe et al 30 .…”
Section: Discussionmentioning
confidence: 90%
“…No research has been found that is directly consistent with these results, but there are studies from which such results can be inferred 30,31 . Research by Onyedibe et al 30 . showed that cancer self‐efficacy is mediating in the relationship between mental adaptation to cancer and health‐related quality of life in cancer patients.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations